Contour scanning for penumbra improvement in pencil beam scanned proton therapy. (24th February 2017) - Meier, G; Leiser, D; Besson, R; Mayor, A; Safai, S; Weber, D C; Lomax, A J
Abstract: Proton therapy, especially in the form of pencil beam scanning (PBS), allows for the delivery of highly conformal dose distributions for complex tumor geometries. However, due to scattering of protons inside the patient, lateral dose gradients cannot be arbitrarily steep, which is of importance in cases with organs at risk (OARs) in close proximity to, or overlapping with, planning target volumes (PTVs). In the PBS approach, physical pencil beams are planned using a regular grid orthogonal to the beam direction. In this work, we propose an alternative to this commonly used approach where pencil beams are placed on an irregular grid along concentric paths based on the target contour. Contour driven pencil beam placement is expected to improve dose confirmation by allowing the optimizer to best enhance the penumbra of irregularly shaped targets using edge enhancement. Its effectiveness has been shown to improve dose confirmation to the target volume and reduce doses to OARs in head-and-neck planning studies. Furthermore, the deliverability of such plans, as well as the dosimetric improvements over conventional grid-based plans, have been confirmed in first phantom based verifications.